Study on factors that contribute to social networks development among students at Universiti Teknikal Malaysia (UTeM) Melaka / Munzir Azizi Mohd Abbas Buskaran and Mohd Syazani Ali Mohtar - Mohd Abbas Buskaran, Munzir Azizi; Ali Mohtar, Mohd Syazani (Faculty of Administrative Science and Policy Studies, 2012)
Sociability, status and hedonic motive are the factors that contribute towards social networks development among students. Sociability motive is referring to the users using the social networks to fulfill their social need such as sense of loving, belonging and interacting with others. Status motive refers to which sharing information through social networks is perceived to be effective in enhancing social status in one’s social group. Hedonic motive refers to the users that engaged with social networks because they believe that these technology will help them to release their tensions or stress and at the same time give them enjoyment and happiness. This study examines the significant relationship between factors, the most dominant factor(s) that contribute to the development of social networks among students and the most popular social networks channel used by the students. This study was conducted at Universiti Teknikal Malaysia (UTeM) Melaka. Then the respondents were chosen by using convenience sampling to distribute the questionnaire. According to the findings, it shows that sociability motive, status motive and hedonic motive are contribute to the development of social networks and also Facebook become most popular social networks channel used by the student at Universiti Teknikal Malaysia (UTeM) Melaka.